Design of Hydrogel Silk-Based Microarrays and Molecular Beacons for Reagentless Point-of-Care Diagnostics - Sampieri, Alicia; Monroy-Contreras, Ricardo; Asanov, Alexander; Vaca, Luis (Frontiers in Bioengineering and Biotechnology, 2022)
We have developed a novel microarray system based on two technologies: 1) molecular beacons designed to interact with DNA targets at room temperature, and 2) tridimensional silk-based microarrays containing the molecular beacons immerse in the silk hydrogel. Unlike conventional microarrays that exhibit reduced signal-to-background ratio, require several stages of incubation, rinsing and stringency control, and measure only end-point results; our microarray technology provides enhanced signal-to-background ratio, performs analysis rapidly in one step without the need for labeling DNA targets and measures the entire course of association kinetics between target DNA and the molecular beacons. To illustrate the benefits of our technology we conducted microarray assays designed for the identification of influenza viruses. We show that in a single microarray slide we can identify the virus subtype according to the molecular beacons designed for hemagglutinin (H1, H2 and H3) and neuraminidase (N1, N2). We also show the identification of human and swine influenzas using sequence-specific molecular beacons. This microarray technology can be easily implemented for reagentless point-of-care diagnostics of several contagious diseases, including coronavirus variants responsible for the present pandemic.